1985
DOI: 10.1007/bf01534703
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal localization of three humanras genes by in situ molecular hybridization

Abstract: Three human ras family protooncogenes, c-Ki-ras-1, and c-Ki-ras-2, and N-ras, have been mapped to chromosome bands 6p11-12, 12p11.1-12.1, and 1p11-13, respectively by in situ molecular hybridization. Certain human cancers display consistent and specific alterations involving chromosomes 1, 6, and 12. The precise chromosomal localization of ras genes will permit evaluation of the possible effect of these chromosome changes on the structure and activities of ras protooncogenes in human neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 52 publications
0
30
0
1
Order By: Relevance
“…Theoretically, between 25 ± 50 genes could be present within such a stretch of DNA. However, SOX5, JAW1 and KRAS2 are the only genes which were so far mapped within this SROA (Popescu et al, 1985;Wunderle et al, 1996 and this manuscript). The human SOX5 gene was only very recently described.…”
Section: Discussionmentioning
confidence: 69%
“…Theoretically, between 25 ± 50 genes could be present within such a stretch of DNA. However, SOX5, JAW1 and KRAS2 are the only genes which were so far mapped within this SROA (Popescu et al, 1985;Wunderle et al, 1996 and this manuscript). The human SOX5 gene was only very recently described.…”
Section: Discussionmentioning
confidence: 69%
“…The cellular and molecular mechanisms conferring oncogenic effects and activating KRAS mutations remain incompletely understood (Simi et al, 2008). Studies have showed that activation of the mitogen-activated protein kinase pathway was important for the development of colorectal cancer via BRAF or KRAS mutations (Popescu et al, 1985). Thus, in this study, we examined whether the BRAF and KRAS gene have the same effect in breast cancer.…”
Section: Introductionmentioning
confidence: 97%
“…These less prominent fragments indicate the presence of additional JUN-like gene(s) on a different chromosome in the human genome. To confirm concordancy of human chromosome 1 and the major JUN 7.0-kbp fragment in the hybrid panel, filters were routinely stripped of probe and rehybridized to N-RAS and a-spectrin (SPTA) probes, which have been mapped to lp and lq, respectively (14,19 A summary of all somatic cell hybrid data is presented in Fig. 2.…”
Section: Resultsmentioning
confidence: 99%